The MAJOR PUBLIC EVENT at the John Curtin Gallery that launched Permeable Boundaries: a field of possibilities - Smith, Dianne; Lommerse, Marina (John Curtin Gallery, 2010)
Research Background :: This event served to bring the industry, profession, educators and students together to reflect on the nature of Interior Architecture (IA), to challenge preconceptions, and to choreograph a number of significant aspects of Interior Architecture into the evening. The design and production of the event took on a dynamic and experiential form involving the manipulation of space through a projected evolving over-scaled graphic-image installation and the integration of formalities including international guest speaker Patrick Chong, 3Design+Asia Group and the Minister for the Arts. This culminated with a moving mime-performance by disguised senior students through the audience to depict their understandings of Interior Architecture. The qualities of fluidity and impermanence that characterise interior architecture within research and practice were thereby experienced first hand to complement the exhibition held in the individual gallery space at the John Curtin Gallery.Research Contribution :: The event was conceived as a conduit, which on the night served to reinforce and demonstrate the emerging concepts of Interior Architecture as ‘a field’ that offers permeability yet definition. As did the exhibition, its creation evolved as the researchers understandings of the Interior was solidified over the project. The major research contribution was the redefinition of the profession of IA in the contemporary in the University education arena as well as complementing the abstract concepts that define what Interior Architecture is; and, how the design of an event is the core business of IA Practice and thereby modelling through the creative practice.Research Significance :: The action research model produced an event that positioned Interior Architecture within a contemporary way of considering education and practice. It included a Catalogue, with significant contributors, which was distributed through the CU bookstore and John Curtin Gallery as well as by mail order. The catalogue relates the analysis of the data collected and the conceptualisation of the Discipline. It included furniture piece by Penelope Forlano demonstrating cutting edge detailing and making as well as design. It integrated the work of 20 practitioners spanning a breadth of destinations and career paths. It also engaged the audience, with immediacy through interactive dimensions, in the concepts.PROOF OF PRESTIGIOUS QUALITY :: Held in prestigious gallery, John Curtin Gallery - Supported by the Vice Chancellor of Curtin University - Won a Pro Vice Chancellor’s 2010 award for Excellence - Attracted 300 members of the profession, industry and educators - Received publicity through local media and nationally through InDesign e-magazine